Análisis del lenguaje especializado en el periodismo económico fiscal, diario el comercio, periodo octubre 2016 a marzo 2017. - Saltos Gavilanes, Jazmin Estefania (2018)
The present research makes an analysis of the specialized language used at the Fiscal Economic Journalism in El Comercio newspaper, from October 2016 to March 2017. It concerns about the lack of specialized professionals in this área, the little space that they have in the media, the treatment of economic information and the loss confidence of the audience for this kind of information. The communication around of the economic activity is not a current phenomenon, but it goes back to the classic text of journalism of the XV and XVI centuries, controlled by the German commercial house of the Függer and by the British commercial agent Thomas Greshman (Del Rio, 2004). In this way journalists become mediators between experts and citizens, demanding a specialization in this área; it is here where the fiscal economic journalism gave origin, that focuses on providing information on the Government´s economic activities. This research is descriptive and documentary, the methods used are: scientific, qualitative and quantitative; the data collection techniques and documentary analysis are developed, 383 from the surveyed population of Riobamba town in 5 urban parishes and content analysis using the data table, with information obtained from El Comercio newspaper printed versión. Which resulted in 58.08% of surveyed people do not know the technical terms used in the economic journal notes of fiscal nature.